Techniques for better vario-scale map content - Šuba, Radan (A+BE | Architecture and the Built Environment, 2018)
The previous chapters covered the research where the vario-scale structure has been introduced. The main aim of the research was general functionality, performance and optimization. So far, the technical aspects had higher priority than the map content. Therefore, this chapter focuses on improving our development kit for generating varioscale content. It presents a strategy to provide good cartographic results throughout all scales and properly stored in the structure. First, Section 4.1 specifies our target. Section 4.2 presents solutions of other researchers. Section 4.3 introduces concepts and tools which are used later in newly designed process. This is demonstrated on road features in Section 4.4. The section presents the generalization approach for the whole scale range from large scale, where roads are represented as area objects, to mid and small scales, where roads are represented as line objects. In our suggested gradual approach even for one road the representation can be mixed, both area and line, which may provide better transition phase and be